Granular Flow Impact Forces on Protection Structures: MPM Numerical Simulations with Different Constitutive Models. (2016) - Ceccato, Francesca; Simonini, Paolo
Abstract: Flows of granular materials are among the most destructive of all landslide phenomena. The assessment of the potential damage caused by the granular flow and the design of protection structures require the knowledge of the landslide-structure interaction. Numerical simulations of these phenomena are very complex because large displacements, soil-structure interaction and complex non-linear soil behavior have to be considered. A key issue in the simulation of these phenomena is the definition of a constitutive model able to describe the granular material response under a wide range of strain rates. This study examines and compares the results obtained by different constitutive models, namely the elastic perfectly plastic model with Mohr-Coulomb failure criterion, and the viscoplastic model with Drucker-Prager yielding condition. To this aim, we consider a finite volume of granular material instantaneously released from the top of an inclined channel; the material flows downslope and bumps a rigid wall on which the forces are measured.